Postharvest responses of hydroponically grown lettuce varieties to nitrogen application rate - Bevly M. Mampholo; Martin Maboko; Puffy Soundy; Dharini Sivakumar (Journal of Integrative Agriculture, 2019)
Limited information is available on the influence of preharvest N application rates on postharvest quality of different lettuce genotypes. Two green leafy lettuce (Multigreen 1 and Multigreen 3) and red leafy lettuce (Multired 4) were grown in gravel film technique and fertigated with five different N application rates: 60, 90, 120, 150 and 180 mg L−1. The 120 mg L−1 N application is commercially recommended for lettuce. After harvest, lettuce samples were packed in a bioriented poly propylene packaging (5% O2 and 5% CO2) and held at 5°C and 85% RH for 3, 6, 9 and 12 days. The genotypes, preharvest N application rates and storage time affected the leaf colour coordinates, phenolic acids (dicaffeoyltataric acid, caffeoyl tartaric acid, 3-caffeoylquinic acid and 3,4-dihydroxycinnamic acid) and browning enzyme activities (phenylalanine ammonia-lyase (PAL), polyphenol oxidase (PPO) and peroxidase (POD)). Lower rates of N application at preharvest stage showed higher weight loss with the storage time increasing in Multigreen 3. In Multigreen 1, colour coordinate b* value decreased remarkably with N application rates from 60 to 120 mg L−1 due to the onset of browning during storage. While in Multigreen 3 and N application higher than 60 mg L−1 influenced the decrease in b* value. Browning occurred due to the increased activity of PAL enzyme and the availability of the substrates caftaric, chlorogenic, caffeic acids, PPO activity and production of browning pigments due to the activity of POD. Higher, N application rates (>120 mg L−1) influenced the browning mechanism and showed brownish red leaves in Multired 4 during storage. Higher ascorbic acid concentration played a role in reducing the onset of browning in the fresh cuts leaves of Mulitired 4 and Multigreen 3 fertilized with lower preharvest lower N application rates (<120 mg L−1). Preharvest N application at 90 mg L−1 retained the colour, ascorbic acid content and the phenolic acid components and extended the shelf life of Multired 4 lettuce up to 6 days.